Treatment of atopic dermatitis: Recently approved drugs and advanced clinical development programs - Müller, Svenja; Maintz, Laura; Bieber, Thomas (Allergy (Copenhagen), 2024)
Atopic dermatitis (AD) represents the most common skin disease characterized by heterogeneous endophenotypes and a high disease burden. In Europe, six new systemic therapies for AD have been approved: the biologics dupilumab (anti‐interleukin‐4 receptor (IL‐4R) α in 2017), tralokinumab (anti‐IL‐13 in 2021), lebrikizumab (anti‐IL‐13 in 2023), and the oral janus kinase (JAK) inhibitors (JAKi) targeting JAK1/2 (baricitinib in 2020 in the EU) or JAK1 (upadacitinib in 2021 and abrocitinib in 2022). Herein, we give an update on new approvals, long‐term safety, and efficacy. Upadacitinib and abrocitinib have the highest short‐term efficacy among the approved systemic therapies. In responders, dupilumab and tralokinumab catch up regarding long‐term efficacy and incremental clinical benefit within continuous use. Recently, the European Medicines Agency has released recommendations for the use of JAKi in patients at risk (cardiovascular and thromboembolic diseases, malignancies, (former) smoking, and age ≥65 years). Furthermore, we give an overview on emerging therapies currently in Phase III trials. Among the topical therapies, tapinarof (aryl hydrocarbon receptor), ruxolitinib (JAK1/2i), delgocitinib (pan‐JAKi), asivatrep (anti‐transient receptor potential vanilloid), and phosphodiesterase‐4‐inhibitors (roflumilast, difamilast) are discussed. Among systemic therapies, current data on cord‐blood‐derived mesenchymal stem cells, CM310 (anti IL‐4Rα), nemolizumab (anti‐IL‐31RA), anti‐OX40/OX40L‐antibodies, neurokinin‐receptor‐1‐antagonists, and difelikefalin (κ‐opioid‐R) are reported.